2018
DOI: 10.1021/acsomega.8b02826
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Degradation of Polymer Films Using Polyglyoxylate–Polyester Blends and Copolymers

Abstract: Polymeric coatings are commonly employed to alter surface properties. While some coatings are designed to remain stable over a prolonged period, in applications such as pharmaceuticals or fertilizers, the coating is designed to erode and reveal or release the underlying material. Self-immolative polymers (SIPs) undergo depolymerization following the cleavage of stimuli-responsive end-caps from their termini, enabling controlled depolymerization in the solid state and in solution. Poly(ethyl glyoxylate) (PEtG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…An M n of 22 kg/mol was targeted as this chain length allows for wellcontrolled polymerization and easy isolation of the resulting polymer by precipitation in cold methanol. The resulting polymer (PEtG-1) was characterized by 1 H NMR, 13 C NMR, and FT-IR spectroscopic methods, confirming its identity as well as the presence of the alkyne moiety at the terminus (Figures 2, S1, and S10). SEC in DMF revealed that the polymer had an M n of 17.8 kg/mol and Đ of 1.7 relative to PMMA standards (Table 1).…”
Section: ■ Experimentalmentioning
confidence: 75%
See 3 more Smart Citations
“…An M n of 22 kg/mol was targeted as this chain length allows for wellcontrolled polymerization and easy isolation of the resulting polymer by precipitation in cold methanol. The resulting polymer (PEtG-1) was characterized by 1 H NMR, 13 C NMR, and FT-IR spectroscopic methods, confirming its identity as well as the presence of the alkyne moiety at the terminus (Figures 2, S1, and S10). SEC in DMF revealed that the polymer had an M n of 17.8 kg/mol and Đ of 1.7 relative to PMMA standards (Table 1).…”
Section: ■ Experimentalmentioning
confidence: 75%
“…1 H and 13 C NMR spectra were obtained using one of the following instruments: 400 MHz Bruker AvIII HD, 400 MHz Varian INOVA, or 600 MHz Varian INOVA. 1 H NMR chemical shifts were calibrated against the residual solvent signal of CHCl 3 (7.26 ppm) or HOD (4.79 ppm), while 13 C NMR chemical shifts were calibrated against the solvent signal of CDCl 3 (77.16 ppm). FT-IR spectra were obtained using a PerkinElmer FT-IR Spectrum Two instrument with attenuated total reflectance (ATR) sampling.…”
Section: ■ Experimentalmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Additionally, a wide range of trigger endcaps have been reported to date, allowing SIPs to degrade in response to various environmental, chemical, and biological stimuli. 3 These unique properties of SIPs have fueled interest for their use in controlled release systems, [4][5][6][7][8][9][10] stimuli-respon-sive coatings, 11,12 chemical sensors, [13][14][15] and degradable bulk materials. [16][17][18] Since their debut in 2008, 19 a handful of SIP designs have been reported with degradation mechanisms based on 1,4and 1,6-elimination reactions of aromatic compounds, [20][21][22] heterocyclization reactions, 23,24 olefin sulfone elimination reactions, [25][26][27] and the depolymerization of polyacetals.…”
Section: Introductionmentioning
confidence: 99%